Formation and stability of flow-induced nucleation precursors in PCL in the presence of a rigid miscible component. (March 2015) - Guo, Guangmei; Huang, Yajiang; Kong, Miqiu; Yang, Qi; Li, Guangxian
Graphical abstract: Abstract: The influence of a miscible rigid component (styrene- co -acrylonitrile copolymer, SAN) on the formation and relaxation of flow-induced crystal nucleation precursors (FIPs) in poly( ɛ -caprolactone) (PCL) melt was investigated. In situ polarized optical microscopy (POM) experiments suggested that SAN promoted the formation of FIPs but lowered their regularity probably by restricting the mobility of PCL chains and incorporating some shorter molecular chains into FIPs. Sheared blends containing SAN formed fibril FIPs with lower thermal stability but exhibited stronger shear memory effect during subsequent crystallization process. Two dimensional wide-angle X-ray diffraction (2D-WAXD) results showed the orientation degree of crystals in sheared samples decreased with increasing SAN content, probably due to the depressed growth kinetics of kebabs and the relaxation of orientated PCL chains.